Bound Set Selection and Circuit Re-Synthesis for Area/Delay Driven Decomposition - Martinelli, Andres; Dubrova, Elena (Design, Automation and Test in Europe, 2005)
This paper addresses two problems related to disjoint-support decomposition of Boolean functions. First, we present a heuristic for finding a subset of variables, X, which results in the disjoint-support decomposition f(X, Y) = h(g(X), Y) with a good area/delay trade-off. Second, we present a technique for re-synthesis of the original circuit implementing f(X, Y) into a circuit implementing the decomposed representation h(g(X), Y). Preliminary experimental results indicate that the proposed approach has a significant potential.